Antimicrobial Inks: The Anti-Infective Applications of Bioprinted Bacterial Polysaccharides. Issue 11 (November 2019) - McCarthy, Ronan R.; Ullah, Muhammad Wajid; Pei, Eujin; Yang, Guang
Abstract : Bioprinting is a rapidly emerging technology with the potential to transform the biomedical sector. Here, we discuss how a range of bacterial polysaccharides with antibiofilm and antibacterial activity could be used to augment current bioink formulations to improve their biocompatibility and tackle the spread of antibiotic-resistant infections.